2019
DOI: 10.3389/fpubh.2019.00087
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing as Tool for Investigating International Tuberculosis Outbreaks: A Systematic Review

Abstract: Background: Whole-genome sequencing (WGS) can support the investigation of tuberculosis (TB) outbreaks. The technique has been applied to estimate the timing and directionality of transmission and to exclude cases from an investigation. This review assesses how WGS was applied in international outbreak investigations and discusses the advantages and challenges of the application of WGS. Methods: Databases were searched for reports on international TB outbreak investigations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
(95 reference statements)
0
23
0
Order By: Relevance
“…We identified several molecular clusters including isolates from multiple countries, suggesting larger events of international transmission of TB. We expected to find international TB transmission events, also considering previous studies reporting cross-border molecular clusters [ 5 , 7 ]. Looking at the collected metadata, we identified several clusters with multiple isolates from the same patient or multiple autopsy samples collected from the same patient [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We identified several molecular clusters including isolates from multiple countries, suggesting larger events of international transmission of TB. We expected to find international TB transmission events, also considering previous studies reporting cross-border molecular clusters [ 5 , 7 ]. Looking at the collected metadata, we identified several clusters with multiple isolates from the same patient or multiple autopsy samples collected from the same patient [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 84%
“…In comparison, WGS analysis offers a much higher discriminatory power and allows inferring (or excluding) TB transmission at a higher resolution [ 4 ]. In a recent systematic review, van der Werf et al identified three studies that used WGS to investigate the international transmission of TB [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of publications demonstrated the utility of M. tuberculosis WGS in critical situations, such as international outbreaks [12]. For instance, a recent study demonstrated the presence of a circulating cluster of multidrug-resistant TB (MDR-TB) strains in European countries involving patients from countries of the African Horn and Sudan [13].…”
Section: Introductionmentioning
confidence: 99%
“…We identified several molecular clusters including isolates from multiple countries, suggesting larger events of international transmission of TB. We expected to find international TB-transmission events, also considering previous studies reporting cross-border molecular clusters [5, 7]. Looking at the collected metadata, we identified several clusters with multiple isolates from the same patient or multiple autopsy samples collected from the same patient [29, 30].…”
Section: Discussionmentioning
confidence: 75%
“…In comparison, WGS analysis offers a much higher discriminatory power and allows for inferring (or excluding) TB transmission at a higher resolution [4]. In a recent systematic review, van der Werf and co-authors identified three studies that used WGS to investigate the international transmission of TB [7].…”
Section: Introductionmentioning
confidence: 99%